Nuclear modification of Y states in pPb collisions at ?SNN=5.02 TeV - Tumasyan, A.; Adam, W.; Ambrogi, F.; Bergauer, T.; Dragicevic, M.; Ero, J.; Del Valle, A. Escalante (Elsevier, 2022)
Production cross sections of Y(1S), Y(2S), and Y(3S) states decaying into mu(+)mu(-) in proton-lead (pPb) collisions are reported using data collected by the CMS experiment at root S-NN= 5.02 TeV. A comparison is made with corresponding cross sections obtained with ppdata measured at the same collision energy and scaled by the Pb nucleus mass number. The nuclear modification factor for Y(1S) is found to be R-pPb(Y(1S)) = 0.806 +/- 0.024 (stat)+/- 0.059 (syst). Similar results for the excited states indicate a sequential suppression pattern, such that R-pPb(Y(1S)) > R-pPb(Y(2S)) > R-pPb(Y(3S)). The suppression of all states is much less pronounced in pPbthan in PbPbcollisions, and independent of transverse momentum p(T)(Y) and center-of-mass rapidity y(CM)(Y) of the individual Y state in the studied range p(T)(Y) < 30GeV/c and |y(CM)(Y)| < 1.93. Models that incorporate final-state effects of bottomonia in pPb collisions are in better agreement with the data than those which only assume initial-state modifications. (c) 2022 The Author(s). Published by Elsevier B.V. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/).
Keywords: CMS; Bottomonium; Quarkonium suppression; Quark-gluon plasma; Heavy ion collisions